Impact of the Number of Dissected Lymph Nodes on Survival for Gastric Cancer after Distal Subtotal Gastrectomy. (24th July 2011) - Huang, Chang-Ming; Lin, Jian-Xian; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei; Wang, Jia-Bin
Abstract : Objectives . To investigate the prognostic impact of the number of dissected lymph nodes (LNs) in gastric cancer after curative distal gastrectomy. Methods . The survival of 634 patients who underwent curative distal gastrectomy from 1995 to 2004 was retrieved. Long-term surgical outcomes and associations between the number of dissected LNs and the 5-year survival rate were investigated. Results . The number of dissected LNs was one of the most important prognostic indicators. Among patients with comparable T category, the larger the number of dissected LNs was, the better the survival would be (P < 0.05 ). The linear regression showed that a significant survival improvement based on increasing retrieved LNs for stage II, III and IV (P < 0.05 ). A cut-point analysis yields the greatest variance of survival rate difference at the levels of 15 LNs (stage I), 25 LNs (stage II) and 30 LNs (stage III). Conclusion . The number of dissected LNs is an independent prognostic factor for gastric cancer. To improve the long-term survival of patients with gastric cancer, removing at least 15 LNs for stage I, 25 LNs for stage II, and 30 LNs for stage III patients during curative distal gastrectomy is recommended.